Batman & Robin [videorecording (DVD)] - Schumacher, Joel, 1939-2020-; Schwarzenegger, Arnold; Clooney, George; O'Donnell, Chris; Thurman, Uma; Silverstone, Alicia (Warner Home Video, 1997)
Batman & Robin try to keep their relationship together even as they must stop Mr. Freeze and Poison Ivy from freezing Gotham City.